El derecho penal canónico como ultima ratio: ¿subsidiariedad u obligatoriedad de la acción criminal? (Stato, Chiese e pluralismo confessionale, 2025)
Canon criminal law as ultima ratio: Subsidiarity or obligatory nature of criminal action?Canon criminal law has regained its efficacy in the 21st century after several decades of inaction. Both recent reforms and praxis reveal a canon law “unaccustomed” to dealing with criminal matters, and “disoriented” with respect to its own principles. Canon criminal law is in a state of metamorphosis towards a true system that knows how to weave together canonical principles and those of juridical civilization in accordance with human dignity. In this evolution of canonical criminal law, two principles are key: the principle of criminal legality and the principle of obligatory criminal action. The latter principle entails a reduced and effective canonical criminal law. The reform of canon 1341 has taken a step towards the efficacy of canon criminal law, although it is insufficient: a large part of canon criminal law is still not applied. On the other hand, the question arises as to whether it is possible to speak of the purposes of punishment being satisfied without an official resolution (procedural or procedural). In continuity with the reduction of discretion sought by the 2021 reform, it is proposed to place the concept of ultima ratio in the penal norm, and not in the criminal action.SOMMARIO: 1. Planteamiento - 2. Breve diagnóstico: un derecho penal en metamorfosis - 3. La ultima ratio en los ordenamientos civiles - 4. La ultima ratio en el derecho canónico - 5. Causas sistémicas de la noción canónica de ultima ratio - 6. Concepto de ultima ratio más adecuado en el derecho canónico - 7. Finalidad de la ultima ratio: el retorno a la clásica humanización del derecho penal aportada por el derecho canónico - 8. ¿Pueden existir los fines de la pena sin resolución oficial y pública? - 9. Conclusión: la interpretación sistemática y teleológica del canon.